2015
DOI: 10.1111/pme.12923
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Moderate to Vigorous Physical Activity in Adolescence: An International Population-Based Survey

Abstract: Pain is associated with reduced physical activity in adolescents but this association varies according to gender, age, and the type of pain experienced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…A systematic review of 8 studies investigating the relationship between LBP and physical activity reported positive, negative and non-existent associations 40 . A more recent Danish study found no associations between spinal pain and objectively measured physical activity, either in cross-sectional or longitudinal analyses 41 and a multi-national survey of 400,000 11-15 years olds found that the presence of LBP was generally associated with reduced physical activity, but the size of the relationship was small 42 . See Box 2 for an overview of issues related to impact.…”
Section: Impactmentioning
confidence: 94%
“…A systematic review of 8 studies investigating the relationship between LBP and physical activity reported positive, negative and non-existent associations 40 . A more recent Danish study found no associations between spinal pain and objectively measured physical activity, either in cross-sectional or longitudinal analyses 41 and a multi-national survey of 400,000 11-15 years olds found that the presence of LBP was generally associated with reduced physical activity, but the size of the relationship was small 42 . See Box 2 for an overview of issues related to impact.…”
Section: Impactmentioning
confidence: 94%
“…Adolescence marks a transition in risks for depression and other mental disorders, substance misuse, and antisocial behavior, as well as a fast-track to adulthood with early transitions into sexual activity and school leaving and psychosomatic syndromes [2]. Several common pain syndromes, such as headache, stomachache, back and facial ache, begin or get worse in early adolescence, and these pains more often coexist than occur in isolation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…While more time spent in VPA was significantly associated with a higher probability of reporting pain on shoulders, mid back, knees and ankles/feet. Swain et al [7] found that reduced participation in MVPA was associated with presence of back pain, headache and stomach-ache in girls and also associated with combined headache and stomach-ache or headache in boys. Only one study has investigated the association between objectively measured PA intensity and pain, specifically back and neck pain, in children [10].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Swain et al found that girls who reported reduced participation in MVPA were more likely to have back pain, headache and stomach-ache [7]. Boys who reported reduced participation in MVPA were more likely to have stomach-ache or headache [7]. A third study found that frequent participation in MPA was associated with lower odds of injury among boys, while frequent participation in VPA was associated with higher odds of injury among girls [8].…”
mentioning
confidence: 98%
See 1 more Smart Citation